2023
DOI: 10.1007/s00330-023-09548-6
|View full text |Cite
|
Sign up to set email alerts
|

Does paraspinal muscle morphometry predict functional status and re-operation after lumbar spinal surgery? A systematic review and meta-analysis

Abstract: Objectives Whether paraspinal muscle degeneration is related to poor clinical outcomes after lumbar surgery is still indistinct, which limits its clinical application. This study aimed to evaluate the predictive value of paraspinal muscle morphology on functional status and re-operation after lumbar spinal surgery. Methods A review of the literature was conducted using a total of 6917 articles identified from a search of PubMed, EMBASE, and Web of Science … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 54 publications
0
0
0
Order By: Relevance
“…In recent literature, the role of the paraspinal musculature (PM) has emerged as an important factor affecting spinal pathologies and postoperative complications. 6,7 The PM is composed of the posterior muscles (multifidus and erector spinae) and the anterior psoas muscle. 8 The posterior PM is especially critical for load distribution and stability of the spine by providing intersegmental stabilization and dorsal tension to counteract the anterior to the vertebral column lying center of mass.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…In recent literature, the role of the paraspinal musculature (PM) has emerged as an important factor affecting spinal pathologies and postoperative complications. 6,7 The PM is composed of the posterior muscles (multifidus and erector spinae) and the anterior psoas muscle. 8 The posterior PM is especially critical for load distribution and stability of the spine by providing intersegmental stabilization and dorsal tension to counteract the anterior to the vertebral column lying center of mass.…”
mentioning
confidence: 99%
“…19 A review from Han et al reported strong evidence for an increased risk of bone nonunion, screw loosening, and adjacent segment disease after lumbar fusion in cases of PM atrophy. 7 Despite this mounting evidence, the association between PM and patient-reported outcomes in lumbar fusion surgery is unclear, highlighting a critical area for further research. The goal of this study is to examine how the composition of the PM influences patient-reported outcomes after lumbar decompression and fusion surgery in patients with DLS, with the hypothesis that atrophy of the PM reduces improvements in disability after surgery.…”
mentioning
confidence: 99%
See 2 more Smart Citations